1996
DOI: 10.1073/pnas.93.15.7639
|View full text |Cite
|
Sign up to set email alerts
|

Activation of RAC-protein kinase by heat shock and hyperosmolarity stress through a pathway independent of phosphatidylinositol 3-kinase.

Abstract: RAC protein kinase (RAC-PK), a serine/ threonine protein kinase containing a pleckstrin homology (PH) domain, was activated by cellular stress such as heat shock and hyperosmolarity. Wortmannin, which is known as a potent inhibitor of phosphatidylinositol 3-kinase and normally inhibits growth factor-induced activation of RAC-PK, did not suppress heat-shock induced activation of RAC-PK, indicating that this stress-induced activation of the kinase is not mediated by phosphatidylinositol 3-kinase. The PH domain w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
155
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(167 citation statements)
references
References 40 publications
8
155
4
Order By: Relevance
“…These studies strongly implicated PKB as a downstream effector of growth-factor-stimulated PI-3K activation in a variety of cell types. Subsequently PKB has been shown to be activated by a wide variety of stimuli including haemopoietic cytokines [IL (interleukin)-2, IL-3, IL-4, IL-5], chemokines [formylmethionylleucylphenylalanine, IL-8, RANTES (regulated on activation, normal T-cell expressed and secreted)], heat shock, hyperosmolarity, hypoxia, integrins, the T-cell antigen receptor and nerve growth factor [32][33][34][35][36][37][38][39][40].…”
Section: Phosphatidylinositol 3-kinase (Pi-3k) Mediates Pkb Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies strongly implicated PKB as a downstream effector of growth-factor-stimulated PI-3K activation in a variety of cell types. Subsequently PKB has been shown to be activated by a wide variety of stimuli including haemopoietic cytokines [IL (interleukin)-2, IL-3, IL-4, IL-5], chemokines [formylmethionylleucylphenylalanine, IL-8, RANTES (regulated on activation, normal T-cell expressed and secreted)], heat shock, hyperosmolarity, hypoxia, integrins, the T-cell antigen receptor and nerve growth factor [32][33][34][35][36][37][38][39][40].…”
Section: Phosphatidylinositol 3-kinase (Pi-3k) Mediates Pkb Activationmentioning
confidence: 99%
“…For example, heat-shock-mediated activation of PKB is insensitive to inhibition by wortmannin in some cell types [32]. Agents which raise intracellular cAMP levels can also activate both PI-3K and PKB activity [38,39].…”
Section: Phosphatidylinositol 3-kinase (Pi-3k) Mediates Pkb Activationmentioning
confidence: 99%
“…First, it was shown that Akt is activated by stress signals via mechanisms that are PI3-K-independent (Konishi et al, 1996). More important, the PI3-K-dependent activation of Akt by growth factors was also shown to require phosphorylation (Kohn et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In regard to the upstream regulation of Akt, while the role of PI3-K has well been clari®ed (Franke et al, 1997), a possible involvement of small GTP-binding proteins such as Ras and Rac in IL-3 stimulation of Akt remains obscure. In addition, PI3-K-independent pathway that leads to Akt activation was reported (Konishi et al, 1996).…”
Section: Introductionmentioning
confidence: 99%